2008
DOI: 10.1080/13546780802110131
|View full text |Cite
|
Sign up to set email alerts
|

Getting one step closer to deduction: Introducing an alternative paradigm for transitive inference

Abstract: Transitive inference is claimed to be "deductive". Yet every group/species ever reported apparently uses it. We asked 58 adults to solve 5-term transitive tasks, requiring neither training nor premise learning. A computer-based procedure ensured all premises were continually visible.response-accuracy and RT (non-discriminative nRT) were measured as typically done. We also measured RT confined to correct responses (cRT). Overall, very few typical transitive phenomena emerged. The symbolic distance effect never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 59 publications
(320 reference statements)
1
25
0
Order By: Relevance
“…Relevant to this issue, Goodwin and Johnson-Laird (2006) found that even by the end of adolescence, deductive-transitive-inference has still not fully matured (see also Reyna & Farley, 2006;Wright & Howells, 2008). Goodwin and Johnson-Laird's participants' mean performance never exceeded around 89%, although admittedly their task was very demanding, using transitive problems having two premise-pairs but housing four integrated items (i.e., four-term series) and also using a double-relational comparative (e.g., one premise was of the form John is taller than Peter to a greater extent than Robert is taller than Mike).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Relevant to this issue, Goodwin and Johnson-Laird (2006) found that even by the end of adolescence, deductive-transitive-inference has still not fully matured (see also Reyna & Farley, 2006;Wright & Howells, 2008). Goodwin and Johnson-Laird's participants' mean performance never exceeded around 89%, although admittedly their task was very demanding, using transitive problems having two premise-pairs but housing four integrated items (i.e., four-term series) and also using a double-relational comparative (e.g., one premise was of the form John is taller than Peter to a greater extent than Robert is taller than Mike).…”
Section: Discussionmentioning
confidence: 99%
“…(Klaczynski, 2009, pp.286). It is therefore unsurprising that recent researchers have sought to explain transitivity development from a Dual-Process perspective (Ameel et al, 2007;Bouwmeester et al, 2007;Wright & Howells, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations